Minnesota at a Glance Geologic Time - Southwick, D.L.; Lusardi, B.A.; Dengler, E.L. (Minnesota Geological Survey, 2017)
Short summary of geologic time and age dating of rocks in Minnesota, issued in 1997, revised 2017. Minnesota is host to some of the oldest rocks on Earth; parts of the Morton gneiss in western Minnesota have been dated at 3.5 billion years old. Rocks as old as or older than these are rare on earth because geologic processes on and within our active planet recycle old rocks and produce younger ones (see Minnesota at a Glance: Common Minnesota Rocks). Only in Minnesota, Michigan, northwest Canada, Greenland, Siberia, South Africa, and Australia have remnants of rocks over 3.5 billion years old been preserved. The oldest mineral grains yet identified on Earth are about 4.4 billion years old; they have been found in rocks in Australia that represent sediments recycled from even older rocks. Rocks brought back from the moon by astronauts, and meteorites that have fallen to Earth, are about 4.5 billion years old. Because the moon, Earth, and the meteors probably formed at the same time (concurrently with the rest of the solar system), we can conclude that the Earth itself is about 4.5 billion years old.